MENINGKATKAN HASIL BELAJAR BIOLOGI MELALUI PENGGUNAAN ALAT PERAGA TORSO UNTUK SISWA KELAS XI DI SMAN 12 BUNGO - Friskha Christina Nababan (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This research is based on the background that Biology learning is still not meaningful, the student learning process has not been emphasized on the scientific process so that it has an impact on student learning outcomes. The aim of this research is to improve Biology learning outcomes through the use of Torso teaching aids. This research is classroom action research carried out in 2 cycles in the second semester of 2022/2023. The research subjects were students of class XI IPA.1 SMAN 12 Bungo. Data collection instruments use observation sheets, interviews, tests and documentation. Data was analyzed through qualitative and quantitative approaches. The teacher's observation result in cycle I was 77.7 and the observation result in cycle II was 88.8. Meanwhile, the results of observing student activities in cycle I were 66.6 and the results of observations in cycle II were 86.1. In cycle I the average score obtained was 77.59 with a completion percentage of 62.5%, because in cycle I the indicator of completeness had not been achieved, so cycle II was implemented. In cycle II the average student score was 87.0625 with a learning completion percentage of 87.5%. Based on the research results, it was concluded that the use of torso props could improve the BIology learning process and outcomes of class XI IPA.1 students at SMAN 12 Bungo.